Music for Ages 0 to 3 Years (Journal of Parents and Teachers, 2025)
The article refers to the importance of music for newborns and in the initiation phase where they begin to develop all their senses. Additionally, two songs are suggested for classroom activities, taking into account the objectives, content, activities, and observations.
Keywords: music and education; objectives; start; kids